Comparison of Weight Loss and Comorbidity Improvement Between Laparoscopic Sleeve Gastrectomy and Roux-en-Y Gastric Bypass: A Comprehensive Systematic Review - Mutiara; Hidayat (The Indonesian Journal of General Medicine, 2024)
Background: This study aims to analyze on the comparative outcomes of LSG and RYGB in terms of weight loss, comorbidity resolution, safety profiles, and patient-reported outcomes.  Methods: The review adhered to PRISMA 2020 standards and analyzed full-text English literature from 2014 to 2024. It excluded editorials, review papers from the same journal, and submissions lacking a DOI. Literature sources included PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of  500 articles were retrieved from online databases (PubMed, SagePub, SpringerLink and Google Scholar). After three rounds of screening, ten articles directly relevant to the systematic review were selected for full-text reading and analysis. Conclusion: LSG and RYGB are crucial interventions for combating obesity, providing effective solutions and alleviating associated health issues. Despite similar weight loss and comorbidity improvements, they differ in safety profiles and outcomes. Tailoring treatment approaches based on individual patient factors, surgical proficiency, and ongoing research can optimize bariatric surgery's benefits, promoting long-term health and well-being.